2014
DOI: 10.1021/jp509914w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvent Dielectric Constant and Acidity on the OH Vibration Frequency in Hydrogen-Bonded Complexes of Fluorinated Ethanols

Abstract: Infrared spectroscopy measurements were used to characterize the OH stretching vibrations in a series of similarly structured fluoroethanols, RCH2OH (R = CH3, CH2F, CHF2, CF3), a series which exhibits a systematic increase in the molecule acidity with increasing number of F atoms. This study, which expands our earlier efforts, was carried out in non-hydrogen-bonding solvents comprising molecules with and without a permanent dipole moment, with the former solvents being classified as polar solvents and the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…It can be seen from Figure that the reactivities differed according to the level of fluorination, whereby 2,2,2‐TFE showcased the largest change in %Δ I pa , indicating therefore that it is the most capable of quenching O 2 .− (most reactive), followed by 2,2‐DFE and 2‐FE (least reactive). This is in line with expectations as the strong electron‐withdrawing inductive effects exerted by the highly electronegative F atoms can be reasoned to cause a larger polarization of the O−H bond (thereby increasing its acidity) and also provide greater stabilization and delocalization of the electron density on the alkoxyl radical/alkoxide that is formed after the scavenging reactions with the fluoroethanols ,. Additionally, when comparing the reactivities of the fluorinated and non‐fluorinated derivatives of ethanol, it was noted that the presence of the F atoms resulted in a multi‐fold increment in the reactivities observed …”
Section: Resultssupporting
confidence: 81%
“…It can be seen from Figure that the reactivities differed according to the level of fluorination, whereby 2,2,2‐TFE showcased the largest change in %Δ I pa , indicating therefore that it is the most capable of quenching O 2 .− (most reactive), followed by 2,2‐DFE and 2‐FE (least reactive). This is in line with expectations as the strong electron‐withdrawing inductive effects exerted by the highly electronegative F atoms can be reasoned to cause a larger polarization of the O−H bond (thereby increasing its acidity) and also provide greater stabilization and delocalization of the electron density on the alkoxyl radical/alkoxide that is formed after the scavenging reactions with the fluoroethanols ,. Additionally, when comparing the reactivities of the fluorinated and non‐fluorinated derivatives of ethanol, it was noted that the presence of the F atoms resulted in a multi‐fold increment in the reactivities observed …”
Section: Resultssupporting
confidence: 81%
“…A comparison with the linear fits for the same set of data is shown in Figure S3 (see the Supporting Information), which clearly suggests a nonlinear correlation between the X–H stretching frequency shifts and the proton affinity of the acceptor and the influence of the second-order effects with the increase in the shifts. This is in contrast to several other examples of hydrogen-bonded systems reported in the literature wherein the shifts in the donor stretching frequencies are linearly correlated to the proton affinity of the acceptor. ,,,, On the other hand, Pines et al suggested the possibility of nonlinear correlation between the X–H stretching frequency shifts in the hydrogen-bonded complexes and proton affinities, especially for the stronger bases, which is related to an increase in the anharmonicity and indicates the eventuality of formation of double-well potential along the proton-transfer reaction coordinate. , …”
Section: Resultsmentioning
confidence: 59%
“…This is in contrast to several other examples of hydrogen-bonded systems reported in the literature wherein the shifts in the donor stretching frequencies are linearly correlated to the proton affinity of the acceptor. 14,15,35,38,50 On the other hand, Pines et al 49 suggested the possibility of nonlinear correlation between the X–H stretching frequency shifts in the hydrogen-bonded complexes and proton affinities, especially for the stronger bases, which is related to an increase in the anharmonicity and indicates the eventuality of formation of double-well potential along the proton-transfer reaction coordinate. 49,50…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dielectric constant is one of the most basic properties of fluids. It is fundamental to many aspects of science and technology, including behaviors of biological molecules, 1,2 mechanisms of chemical reactions, [3][4][5] fabrication of new materials, [6][7][8] solubility of polar and nonpolar species, 9,10 and development of energy storage devices. 11 Accurate determination of the dielectric constant from molecular parameters, especially in the liquid phase, remains a challenge, whether theoretically or through computer simulations.…”
Section: Introductionmentioning
confidence: 99%